2000
DOI: 10.1053/lv.2000.6139
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in long-term survivors of pediatric liver transplantation

Abstract: The purpose of this study is to measure the health-related quality of life (HRQOL) in children who are long-term survivors of liver transplantation and to pilot the Liver Transplant Disability Scale (LTDS), a newly developed 12-point scale that quantifies chronic medical disability related to liver transplantation. This study is a crosssectional survey of 51 children surviving liver transplantation by at least 2 years, with a median age of 4.94 years. Functional capacity and utility scores were measured by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 21 publications
0
52
0
Order By: Relevance
“…Table 3 summarizes medical data obtained from liver and kidney transplant recipients within 6 months of survey completion. The LTDS was used to calculate an overall DSD score for each of the 36 liver transplant patients (6). The mean overall LTDS score was 2.04 ± 1.7, corresponding to no disability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 summarizes medical data obtained from liver and kidney transplant recipients within 6 months of survey completion. The LTDS was used to calculate an overall DSD score for each of the 36 liver transplant patients (6). The mean overall LTDS score was 2.04 ± 1.7, corresponding to no disability.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic illness may pose unique dilemmas that directly conflict with the adaptive struggles inherent to adolescent growth and development (1)(2)(3). The focus of care in pediatric patients with chronic diseases is being expanded to ensure satisfactory physical, psychological and social wellness for patients (4)(5)(6)(7)(8)(9)(10)(11). This broadened perspective, which includes attention to healthrelated quality of life (HRQOL), is particularly important in adolescent transplant patients, in whom the psychosocial, emotional and biologic arenas are inherently intermingled.…”
mentioning
confidence: 99%
“…98,99 Older children awaiting liver transplantation for BA also have low-to-average neurocognitive functioning, and the deficits are most severe in children with prolonged illness and malnutrition. A catch-up in neurodevelopment occurs after transplantation (as assessed by testing at 1 year), but deficits may persist, particularly in children who had long hospitalizations and greater nutritional impairment.…”
Section: Improving Outcomes Of Bamentioning
confidence: 99%
“…Medium-term studies (2-10 years after transplantation) have shown that 10%-15% of children with BA have significant neurocognitive deficits (intelligence quotient Ͻ 70), approximately 26% have learning disabilities, and up to 40% require special educational services. 99 Long-term studies of neurological development and cognitive function in children with BA are needed, with a focus on identifying modifiable factors that might prevent or help restore residual deficits. In the meantime, an analysis of resource utilization for educational support services for this growing population of children might help improve access to these necessary aspects of long-term care.…”
Section: Improving Outcomes Of Bamentioning
confidence: 99%
“…Investigators have previously examined quality of life issues in pediatric liver transplant recipients [6][7][8][9][10] and have concluded that, for the most part, quality of life for transplant recipients was good. However, these studies did not use validated instruments and did not address all of the domains that constitute HRQOL.…”
mentioning
confidence: 99%